The multiplication of meanings from micro and small structures in Abdullah Al-Baradouni’s poem titled "From Exile to Exile" - Al-Kindi, Mahmood Yahya (Journal of Arabic Language Sciences and Literature, 2022)
In this research, we tested the role that micro and small structures play in the multiplication of meanings in Abdullah Al-Baradouni’s poem titled "From Exile to Exile". We additionally traced how the meaning rises and grows through prepositions and their connotations when they have their unique morphological nature. We tried to explore how the structures of parallelism and antonym contributed to the production and multiplication of meaning in the text to become a comprehensive meaning in which all structures contributed to the construction of its edifice; the alignment of choices in the text did not only have merely a moral value, but rather, in addition, it had a rhythmic value that reinforced the poeticity, as well as the multiplication of the meaning itself. The multiplication of meaning in this poem was the product of the integration of the small meanings within the contexts of the larger structures. In this research test, we sought stylistic criteria - such as synergy, antonym, parallelism, and juxtaposition - that enabled us to prove our concept that we try to address in this paper.